(untitled) (Medico Legal Update, 2019)
Background/Objectives: The purpose of this consumerism-theory-based study was to explore the types of physical activities favored by students with developmental disabilities using Q methodology. Method/Statistical Analysis: This study used based on a small sample, of less than 30 participants. A total of 27 students with developmental disabilities who were aged between 13 and 18 years, attended special classes at regular schools, and lived in Y city participated in the study. The subjects were classified into 25 physical activity cards developed for this study, and their preference types were analyzed through QUANL pc program. Findings: The results are as follows. First, students with developmental disabilities preferred four types of physical activities. Second, the characteristics of these four types were as follows: peer-centered (first type), family-centered (second type), music-centered (third type), and competition-centered (fourth type). Improvements/Applications: Moreover, these results indicate that students with developmental disabilities are interested in various types of physical activities, and favor a variety of activities types depending on their background characteristics.